Caspofungin versus anidulafungin in patients with invasive candidiasis: a retrospective study with propensity-score-matched analysis - Reem Hasan Elajez (22504292) (2025)
Background Echinocandins are recommended as an initial treatment for invasive candidiasis. Although safety and efficacy profiles of both anidulafungin and caspofungin are well established, direct head-to-head comparisons have not been reported before. Objective Compare efficacy and safety of anidulafungin versus caspofungin among patients with invasive candidiasis. Design Retrospective observational study. Methods Adult patients with invasive candidiasis who were treated with either anidulafungin or caspofungin for ⩾5 days were retrospectively reviewed over a period of 6 years. The primary endpoint was global response, defined as clinical and microbiological success at the end of treatment duration. Results A total of 223 patients who received either anidulafungin ( n = 176) or caspofungin ( n = 47) were initially included. Propensity score matching (based on age, malignancy, level of care, presence of candidemia, and other factors) was performed to improve comparability of the two groups. As a result, 32 patients in the caspofungin arm and 79 patients in the anidulafungin arm were included in the final analysis. Around three-quarters of the cohort had candidemia, and the most common isolated Candida species were C. albicans and C. glabrata . Response rates were comparable between both groups, with the primary outcome of global response showing no significant difference (56.3% for the caspofungin group vs 63.3% for anidulafungin, p = 0.490). Similarly, no differences between the two groups were observed in terms of 90-day all-cause mortality ( p = 0.672) or any other secondary endpoints. Conclusion Our data suggest that anidulafungin and caspofungin have comparable global response among patients with invasive candidiasis. Additionally, both studied echinocandins showed no significant difference in 90-day all-cause mortality. However, due to the limited sample size, larger studies are needed to confirm these results. Other Information Published in: Therapeutic Advances in Infectious Disease License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/20499361251344777